PERFORMANCE ASSESSMENT SYSTEM ARCHITECTURE OF RETAIL SHOPS IN PT. SURABAYA INTERNATIONAL STARS WITH THE BALANCED SCORECARD METHOD - Effendi, Achmad Yusuf; Soebijono, Tony; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. International Stars is a company engaged in the field of distribution that produces sandals and shoes urrently PT. International Stars already has about 400 retail stores that market slippers and shoes. Related to the number of such shops PT. Stars international must monitor the performance of the store with all aspects of assessment include: aspect of revenues, customer satisfaction, as well as aspects of aspects of the performance of the employees at the store. But in the assessment process conducted PT International Stars still use the system manually and computerized and not the result of shaped documents report. So in the manufacturing process and the fulfilment of market strategies will be less fast. In the absence of an accurate assessment of the systems and structured imposes on his old company in response to business growth in the field. Based on these problems, then created a performance assessment application store by using the balanced scorecard method of web-based that can ease the process of assessment and supervision of each store. By displaying the performance results in the form of a nominal or numeric value comparison between stores. Based on the trial results, the performance assessment system of retail stores can help an area sales manager in reporting data for each store with more effective, from the results of the report will also facilitate the operational part in monitoring the results of the development of the whole store.